Monetary policy transmission amid demand reallocations - Julien Bengui; Lu Han; Gaelan MacKenzie (Bank of Canada, 2024)
Large swings in the expenditure shares of goods and services at the start of the pandemic have contributed to the inflation surge, posing new challenges for monetary policy. Using a multi-sector model featuring upward labor adjustment frictions, we analyze the transmission of monetary policy during a demand reallocation episode, focussing on sectoral heterogeneity in inflation and output responses. Following an unexpected contractionary monetary policy shock, (constrained) expanding sectors respond primarily by lowering prices, while (unconstrained) contracting sectors reduce output more significantly. At the aggregate level, monetary policy is thus more effective at curbing inflation when a larger proportion of sectors are expanding or expected to be expanding in the near future.
Keywords: E52; E31; E24; E12; 330; Domestic demand and components; Inflation and prices; Monetary policy transmission